Экспериментальные исследования влияния зоны предразрушения на прочность горной породы при резании - Свешников, И.А.; Майстренко, А.Л.; Заболотный, С.Д.; Виноградова, Е.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
Influence of a zone of predestruction on power indicators of destruction of strong rocks is investigated. It is established, that at repeated cutting of sandstone at the expense of interaction of cracks of a zone of predestruction of size power indicators of destruction appreciably decrease.